2016
DOI: 10.1261/rna.056705.116
|View full text |Cite
|
Sign up to set email alerts
|

Eukaryote-specific rRNA expansion segments function in ribosome biogenesis

Abstract: The secondary structure of ribosomal RNA (rRNA) is largely conserved across all kingdoms of life. However, eukaryotes have evolved extra blocks of rRNA sequences, relative to those of prokaryotes, called expansion segments (ES). A thorough characterization of the potential roles of ES remains to be done, possibly because of limitations in the availability of robust systems to study rRNA mutants. We sought to systematically investigate the potential functions, if any, of the ES in 25S rRNA of Saccharomyces cere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
65
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 51 publications
(68 reference statements)
5
65
0
Order By: Relevance
“…H17, together with H16 and H18, are considered parts of regions characterized as Expansion Segments, where functional insertions have been registered. 32,33 Further study on rRNA structure may help better explain this event.…”
Section: Discussionmentioning
confidence: 99%
“…H17, together with H16 and H18, are considered parts of regions characterized as Expansion Segments, where functional insertions have been registered. 32,33 Further study on rRNA structure may help better explain this event.…”
Section: Discussionmentioning
confidence: 99%
“…ESs exhibit a significant degree of variability between species in length and sequence, plus their size and number of helical branches seem to progressively increase in higher eukaryotes (Michot and Bachellerie 1987). The role of the 28S ESs in ribosomal function is still not clear, but it has recently been shown that they are important in specific steps of the ribosome biogenesis in yeast (Ramesh and Woolford 2016). The many differences we observe between the ESs of maternal-and somatic-type 28S will undoubtedly have an effect on assembly and functioning of the ribosomal LSU.…”
Section: Structural and Functional Implications Of The Lsu Rrna Typesmentioning
confidence: 99%
“…Thus, the arrangement of the srRNAs as well as their anchoring proteins help define the likely order of assembly of the srRNAs, such that stable association of srRNA2 and srRNA3 occurs before that of srRNA1 and srRNA4. Indeed, deletion of the counterpart of srRNA3 in yeast (ES39L) leads to an early processing defect (19). Strikingly, although srRNA1 is the first small rRNA transcribed, it is stably assembled after srRNA2 and srRNA3, suggesting that its RNA processing occurs during or after assembly of the ribosome instead of the 5′ to 3′ direction following transcription.…”
Section: Significancementioning
confidence: 99%
“…This helix contacts extensions of eL8 and interacts with the 3′-end of the 5.8S rRNA. In yeast, deleting ES31L or the N-terminal extension of eL8 blocks ribosome assembly at later stages, suggesting that ES31L may be involved in subsequent stabilization steps of the previously established scaffold (23). Also associated with the later stages is the final positioning of the 5S rRNA.…”
Section: Significancementioning
confidence: 99%